Novel histopathological approaches for treatment guidance in head and neck squamous cell carcinoma - Koskenniemi, Anna-Riina (fi=Turun yliopisto|en=University of Turku|, 2026)
Head and neck squamous cell carcinoma (HNSCC) is a clinically and biologically heterogeneous malignancy that continues to pose major therapeutic challenges. As combination treatment strategies expand, practical biomarkers are needed to refine prognostication and guide treatment selection beyond conventional staging. This thesis identified histopathological and immunological biomarkers relevant to treatment guidance in HNSCC, with a particular focus on neoadjuvant radiotherapy and chemoradiotherapy (RT/CRT), and evaluated artificial intelligence (AI) for standardized morphologic assessment while investigating the clinical relevance of the cancer–germline antigen DEAD-box helicase 4 (DDX4). Altogether, cancer tissues from 270 HNSCC patients were examined. In a retrospective neoadjuvant cohort with paired pre- and post-treatment specimens (n=53), analyses included immune profiling by immunohistochemistry (CD8, CD68, CD206, Clever-1, and PD-L1), deep learning–based quantification of pretreatment tumor necrosis, and post-treatment response assessment using a pragmatic two-tier combined metric (cHTR) that integrates regression measures with the histiocytic multinucleated giant cell reaction (MGC) as a novel component. Pretreatment necrosis was a strong marker of poor outcome in neoadjuvant RT/CRT-treated HNSCC, and AI enabled reproducible, high-throughput necrosis quantification. The cHTR provided robust prognostic stratification, while higher baseline PD-L1 expression and increased intraepithelial CD8⁺ TILs were associated with poorer cHTR. DDX4 formed tumor-associated germ-granule–like cytoplasmic ribonucleoprotein granules, and its loss altered gene regulation and attenuated malignant phenotypes, including impaired xenograft tumor formation. Notably, pretreatment DDX4 positivity predicted favorable cHTR in neoadjuvant RT/CRT treated HNSCC. In conclusion, these findings may contribute to more individualized treatment strategies in HNSCC.